2019
DOI: 10.1136/thoraxjnl-2018-212456
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of second and higher order smoking-related primary cancers following lung cancer: a population-based cohort study

Abstract: BackgroundLung cancer 5-year survival has doubled over 15 years. Although the risk of second primary cancer is recognised, quantification over time is lacking. We describe the incidence of second and higher order smoking-related primary cancers in lung cancer survivors, identifying high-incidence groups and how incidence changes over time from first diagnosis.MethodsData on smoking-related primary cancers (lung, laryngeal, head and neck, oesophageal squamous cell carcinoma and bladder) diagnosed in England bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 20 publications
(16 reference statements)
2
33
0
Order By: Relevance
“…Although the carcinogenic effects of tobacco smoking and alcohol are widely described (Do et al., 2004), the included studies did not reported data for these risk factors before and after the primary diagnosis, probably because they used cancer registries databases, which did not report this information. Our findings are in line with the published evidence of increased SPC risk among HNC patients with alcohol and tobacco consumption (Barclay et al., 2019). The HPV status was not available in the studies pooled in the primary analyses; thus, the direct effect of HPV infection is difficult to distinguish from the effects of smoking and alcohol consumption.…”
Section: Discussionsupporting
confidence: 94%
“…Although the carcinogenic effects of tobacco smoking and alcohol are widely described (Do et al., 2004), the included studies did not reported data for these risk factors before and after the primary diagnosis, probably because they used cancer registries databases, which did not report this information. Our findings are in line with the published evidence of increased SPC risk among HNC patients with alcohol and tobacco consumption (Barclay et al., 2019). The HPV status was not available in the studies pooled in the primary analyses; thus, the direct effect of HPV infection is difficult to distinguish from the effects of smoking and alcohol consumption.…”
Section: Discussionsupporting
confidence: 94%
“…Even with advancement in medical technology, the five year survival rate was still devastating in advanced LC patients. Various factors can increase the risk of LC; smoking is a leading cause [24]. There is also evidence of a link between consumption of alcohol without food and high incidence of LC [25].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, it was reported that more than 8% of these survivors were facing the probability of progressing a second primary malignancy (SPM) ( 5 ) and SPM becomes one of the main causes of death for those patients ( 6 ). Hence, there are a growing number of studies exploring the risk factors of SPM in different cancer survivors such as breast ( 7 ), lung ( 8 ) as well as colorectal cancer ( 9 , 10 ). However, these studies used logistic regressions or Cox proportional hazard regressions to analyze SPM-related factors, which ignored the death as a competing event for occurring PSMs.…”
Section: Introductionmentioning
confidence: 99%